An AIE‐Active Conjugated Polymer with High ROS‐Generation Ability and Biocompatibility for Efficient Photodynamic Therapy of Bacterial Infections. (11th March 2020) - Zhou, Taotao; Hu, Rong; Wang, Lirong; Qiu, Yanping; Zhang, Guiquan; Deng, Qiyun; Zhang, Haiyan; Yin, Pingan; Situ, Bo; Zhan, Chunlie; Qin, Anjun; Tang, Ben Zhong
Abstract: New, biocompatible materials with favorable antibacterial activity are highly desirable. In this work, we develop a unique conjugated polymer featuring aggregation‐induced emission (AIE) for reliable bacterial eradication. Thanks to the AIE and donor‐π‐acceptor structure, this polymer shows a high reactive oxygen species (ROS)‐generation ability compared to a low‐mass model compound and the common photosensitizer Chlorin E6. Moreover, the selective binding of pathogenic microorganisms over mammalian cells was found, demonstrating its biocompatibility. The effective growth inhibition of bacteria upon polymer treatment under light irradiation was validated in vitro and in vivo. Notably, the recovery from infection after treatment with our polymer is faster than that with cefalotin. Thus, this polymer holds great promise in fighting against bacteria‐related infections in practical applications. Abstract : Desinfektion mit Sonnenlicht : Ein Benzothiadiazol und Tetraphenylethen enthaltendes Polymer (PTB‐APFB) mit hoher Aktivität in der Generierung reaktiver Sauerstoffspezies sowie hoher Selektivität für pathogene Mikroorganismen gegenüber Säugetierzellen wurde entwickelt. In‐vitro‐ und In‐vivo‐Ergebnisse zeigen, dass PTB‐APFB effizient das Wachstum von Bakterien hemmt, was die Genesungszeit von Infektionen gegenüber Cefalotin um 3 Tage verringert.